On the performance of recency-rank and block-sorting universal lossless data compression algorithms - Muramatsu, J. (Information Theory: 2000 IEEE International Symposium On, 2000)
We present bounds of the redundancy of the recency-rank and the block-sorting universal lossless data compression algorithms for finite-length sequences.